(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This scientific article explores the importance of introducing financial literacy education in school curricula. In the modern global economy, individuals are expected to manage personal finances, understand budgeting, savings, credit systems, and financial planning from an early age. However, many young people enter adulthood without sufficient financial knowledge, which often leads to poor financial decisions and long-term economic difficulties. This study analyzes the role of schools in developing financial awareness, the benefits of financial education, and the challenges of implementing it in educational systems. The findings suggest that financial literacy is a crucial life skill that should be integrated into school education to prepare students for real-world financial responsibilities.